2015
DOI: 10.1021/acs.orglett.5b01695
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formed Acetal-Facilitated Synthesis of Substituted Indene Derivatives from o-Alkenylbenzaldehydes

Abstract: A new protocol has been developed for the synthesis of indene derivatives in a diastereoselective manner from o-alkenylbenzaldehydes and enolizable ketones in the presence of trimethyl orthoformate and catalytic triflic acid. This method involves tandem in situ formed acetal-assisted Claisen-Schmidt condensation followed by 5-exo-trig cyclization/Michael addition in one-pot. It has also been shown that the chalcones derived from o-alkenylbenzaldehydes and ketones can effectively be transformed into indene deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Proceeding on the same line, Balamurugan et al [81] . also established a fast and expedient in situ generated acetal‐promoted protocol for diastereoselective synthesis of indene derivatives (Scheme 51).…”
Section: Neutral Additives‐induced Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proceeding on the same line, Balamurugan et al [81] . also established a fast and expedient in situ generated acetal‐promoted protocol for diastereoselective synthesis of indene derivatives (Scheme 51).…”
Section: Neutral Additives‐induced Reactionsmentioning
confidence: 99%
“…Subsequently, I161 might undergo two different pathways to afford naphthalene product 135, and the intervention of HC(OMe) 3 might also be involved in the late stage. Proceeding on the same line, Balamurugan et al [81] also established a fast and expedient in situ generated acetalpromoted protocol for diastereoselective synthesis of indene derivatives (Scheme 51). The orthoformate additive, HC Control experiments shown that a compound 139 can be converted readily into 140 in the absence of HC(OMe) 3 with the aid of TfOH catalyst.…”
Section: Orthoformatesmentioning
confidence: 99%
“…In the experiment, fully deuterated trimethyl orthoformate (DC(OCD 3 ) 3 ) was used in place of trimethyl orthoformate under the optimized conditions that showed deuterium incorporation at C2 of the 1-acylnaphthalene 583 . 102…”
Section: Lewis Acid Catalyzed Reactionsmentioning
confidence: 99%
“…Iodine-promoted and base-promoted cyclization reactions have been reported. Lewis and Brønsted acid-catalyzed reactions of alkene conjugate addition have been studied . It is desirable to find new efficient methods to construct variously functionalized indene derivatives.…”
Section: Introductionmentioning
confidence: 99%